2002
DOI: 10.1136/fn.87.1.f55
|View full text |Cite
|
Sign up to set email alerts
|

A three year follow up of preterm infants after moderately early treatment with dexamethasone

Abstract: Objective: To assess the effect of moderately early postnatal dexamethasone treatment on growth and neurodevelopmental outcome in preterm infants. Methods: Thirty preterm infants enrolled in a randomised clinical trial to investigate the effectiveness of moderately early dexamethasone administration in the treatment of chronic lung disease were routinely followed up. Fifteen babies received a total dose of 4.75 mg/kg over 14 days from the 10th day of life, and 15 babies were untreated. Five infants in each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…In some studies, treatment of premature infants with Dexa was associated with decreased longitudinal growth (Wood et al 2003, Rijken et al 2007, but this was not confirmed by others (Halliday 2001, Romagnoli et al 2002. Interestingly, premature infants with a relative insensitivity to glucocorticoids, exhibit a complete catch-up growth during the first 2 years of life while infants without this polymorphism remain below the mean height for the normal population up to 19 years of age (Finken et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, treatment of premature infants with Dexa was associated with decreased longitudinal growth (Wood et al 2003, Rijken et al 2007, but this was not confirmed by others (Halliday 2001, Romagnoli et al 2002. Interestingly, premature infants with a relative insensitivity to glucocorticoids, exhibit a complete catch-up growth during the first 2 years of life while infants without this polymorphism remain below the mean height for the normal population up to 19 years of age (Finken et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 10% of them length remains below the –2 SDS line [65]. Most studies have shown that postnatal corticosteroid treatment has a negative effect on postnatal catch-up [64, 82, 83], but others did not find such effect [61,84,85,86]. Other factors that have been negatively related to later (catch-up) growth in preterm infants include male gender [3], medical complications [87] and being born SGA [60,61,62,63, 88].…”
Section: Catch-up Growthmentioning
confidence: 99%
“…The study was approved by the Institutional Review Board and parents' informed consent was obtained. The following exclusion criteria were adopted: intrauterine growth retardation (birth weight ϽϪ2 SD), congenital metabolic disorders, chromosomal imbalance syndromes, congenital infection syndromes, rickets (maternal osteomalacia), maldigestion, malabsorption, neuromuscular disorders, renal or endocrinological diseases, or dexamethasone treatment (17,18). Length and weight were measured at the time of assessment.…”
mentioning
confidence: 99%